Generic semi-automated radiofluorination strategy for single domain antibodies: [18F]FB-labelled single domain antibodies for PET imaging of fibroblast activation protein-α or folate receptor-α overexpression in cancer - Herlinde Dierick; Laurent Navarro; Hannelore Ceuppens; Thomas Ertveldt; Ana Rita Pombo Antunes; Marleen Keyaerts; Nick Devoogdt; Karine Breckpot; Matthias D'Huyvetter; Tony Lahoutte; Vicky Caveliers; Jessica Bridoux (SpringerOpen, 2024)
Abstract Background Radiofluorination of single domain antibodies (sdAbs) via N-succinimidyl-4-[18F]fluorobenzoate ([18F]SFB) has shown to be a promising strategy in the development of sdAb-based PET tracers. While automation of the prosthetic group (PG) [18F]SFB production, has been successfully reported, no practical method for large scale sdAb labelling has been reported. Therefore, we optimized and automated the PG production, enabling a subsequently efficient manual conjugation reaction to an anti-fibroblast activation protein (FAP)-α sdAb (4AH29) and an anti-folate receptor (FR)-α sdAb (2BD42). Both the alpha isoform of FAP and the FR are established tumour markers. FAP-α is known to be overexpressed mainly by cancer-associated fibroblasts in breast, ovarian, and other cancers, while its expression in normal tissues is low or undetectable. FR-α has an elevated expression in epithelial cancers, such as ovarian, brain and lung cancers. Non-invasive imaging techniques, such as PET-imaging, using tracers targeting specific tumour markers can provide molecular information over both the tumour and its environment, which aides in the diagnosis, therapy selection and assessment of the cancer treatment. Results [18F]SFB was synthesized using a fully automated three-step, one-pot reaction. The total procedure time was 54 min and results in [18F]SFB with a RCP > 90% and a RCY d.c. of 44 ± 4% (n = 13). The manual conjugation reaction after purification produced [18F]FB-sdAbs with a RCP > 95%, an end of synthesis activity > 600 MBq and an apparent molar activity > 10 GBq/µmol. Overall RCY d.c., corrected to the trapping of [18F]F− on the QMA, were 9% (n = 1) and 5 ± 2% (n = 3) for [18F]FB-2BD42 and [18F]FB-4AH29, respectively. Conclusion [18F]SFB synthesis was successfully automated and upscaled on a Trasis AllInOne module. The anti-hFAP-α and anti-hFR-α sdAbs were radiofluorinated, yielding similar RCYs d.c. and RCPs, showing the potential of this method as a generic radiofluorination strategy for sdAbs. The radiofluorinated sdAbs showed a favourable biodistribution pattern and are attractive for further characterization as new PET tracers for FAP-α and FR-α imaging.